Diversidade e distribuição de siris (Decapoda: Brachyura: Portunidae) e dinâmica populacional de Callinectes ornatus no litoral norte de São Paulo - Hippólito, Michele Furlan de [UNESP] (2014)
The aim of this study was to analyze the composition, abundance and diversity of swimming crabs of unconsolidated substrate at depths up to 35 m, in two distinct regions of the northern coast of São Paulo. Additionally, the influence of the sediment and water temperature on the diversity and abundance of portunid crabs was analyzed. The samples were collected using a commercial shrimp trawler equipped with double-rig nets. The crabs and environmental variables were sampled monthly during two years, at depths from 5 to 35 m in Ubatuba (UBA) and Caraguatatuba (CAR) regions. Richness (S), diversity (H'), evenness and dominance values were determined in each depth and season. Eight species of portunid crabs were obtained (SUBA = 8 and SCAR = 7), totaling 19,287 individuals collected during study period (UBA = 9,645 and CAR = 9,642). The depths with the highest richness values (UBA: 5 m and CAR: 15 m) were not necessarily those with the highest diversity and evenness values (UBA: 20 m and CAR: 5 m). Temporally, the seasons with the highest diversity and evenness (UBA: winter 01 and autumn 03, CAR: winter 01 and autumn 02) were the seasons which showed the highest richness (UBA: winter 01, summer 02 and autumn 02-03, CAR: autumn 02). The highest dominance values were recorded in sites and periods with the smallest diversity indexes, and vice versa. Phi (sediment) and temperature did not correlate significantly with the diversity but correlated with the abundance of individuals. Among the species obtained, Charybdis hellerii, Cronius ruber and Portunus ordwayi presented, all together, relative abundance smaller than 0.1% in each region, while Callinectes ornatus and Portunus spinicarpus comprised more than 80% of the total abundance. The highest abundance of the latter species varied differently among the depths and seasons. Sites and periods with the highest diversity indexes are related to the great uniformity of the number of individuals ...